Leks - Höglund, Jacob, 1958-; Alatalo, Rauno V. (Monographs in behavior and ecology., 1995)
The evolution of leks--clusters of small territories where males congregate and display in order to attract mates--is of central issue in behavioral ecology, because of the insights it offers into female mate choice, sexual selection, and the evolution of mating systems. In the first book on the subject, Jacob Höglund and Rauno Alatalo draw together existing knowledge on two main aspects of lekking. Why do leks evolve in some species and not in others? Why do females of certain lekking species select their mates even though such behavior reaps few or no material benefits for them? In each case they emphasize the importance of understanding the selective forces that act on individuals in natural populations.Höglund and Alatalo synthesize the available information on lekking in all animal groups and suggest new areas of research.Originally published in 1995.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.